New Insights in Cytokines in Childhood Obesity: Changes in TWEAK and CD163 After a 2-Year Intervention Program in Prepubertal Children With Obesity - Escartín, Rocío; Font, Maria; González-Clemente, José Miguel; Vendrell, Joan; Caixàs, Assumpta; Corripio, Raquel (Frontiers in Endocrinology, 2022)
Objective Obesity is characterized by a low-grade inflammatory state in adipose tissue. Tumor Necrosis Factor Weak Inducer of Apoptosis (TWEAK) and Cluster of Differentiation 163 (CD163) are cytokines potentially involved in the pathogenesis of obesity. Little is known about them in children. The aim of this study was to observe serum levels of TWEAK and CD163 in prepubertal children with obesity compared to lean, and to evaluate its changes after a 2-year intervention program in children with obesity. Methods Case-control study with a prospective follow-up of cases for 2 years in a referral pediatric endocrine outpatient centre. Seventy-three prepubertal children with obesity, and 47 age- and gender-matched lean controls were studied. Sixty-two cases finished the program. Anthropometric parameters, Homeostatic Model Assessment for Insulin Resistance (HOMA-IR), lipid profile, and concentrations of TWEAK and CD163 were determined. Children with obesity were re-evaluated after a 2-year intervention program consisting of diet and exercise. Weight loss was considered if z-score Body Mass Index (BMI) decreased at least 0.5 Standard Deviations (SD). Results We observed higher CD163 levels in children with obesity compared to controls. No significant differences were observed in TWEAK and CD163/TWEAK ratio at baseline. After the 2-year intervention program, TWEAK levels were higher and CD163/TWEAK ratio was lower in children with weight loss than those without weight loss. CD163 decreased in both groups. Conclusion TWEAK and CD163 seem to have a role in the pathogenesis of obesity in prepubertal children.